ANALISIS POTENSI SENTRA INDUSTRI DI KECAMATAN BENGKALIS DAN KECAMATAN BANTAN BERDASARKAN SEKTOR UNGGULAN DI KABUPATEN BENGKALIS - Erik Maunanta; Jahrizal Jahrizal; Ando Fahda Aulia (Program Studi Pendidikan Ekonomi Universitas Riau, 2021)
The purpose of this study was to determine and analyze the potential of commodity-based industrial centers in Bengkalis and Bantan Districts and to find out what superior commodities are in Bengkalis and Bantan districts. The analysis was carried out by descriptive method, using a combined approach, namely quantitative and qualitative. The unit of analysis in this research is Bengkalis Regency, namely in two locations, namely Bengkalis District and Bantan District. The results of the analysis show that Bengkalis Regency is an area that has a strategic geographical location. Main commodities in Bengkalis and Bantan Subdistricts, Bengkalis districts, are food and horticulture, plantation, livestock and fisheries sectors. Which these sectors have a comparative advantage and have export opportunities to other regions (both outside the district and district).